Big five personality traits and employability: The mediating role of internship attitudes among chinese vocational students. - Sixiao Hu; Mohd Khata Jabor; Hongbin Fang; Dapeng Sun; Yiqing Zheng; Yunzhuo Wu; Yuefan Zhao; Yuanyuan Zhao; Ninglin Li; Xiaohong Zhao (PLoS ONE)
This study investigates the impact of the Big Five personality traits on the employability of vocational education students, with a focus on the mediating role of internship attitudes. Data were collected from 550 students enrolled in 11 vocational colleges in Hebei Province, China, using a structured questionnaire. Structural Equation Modeling (SEM) was employed to analyze the relationships among personality traits, internship attitudes, and employability. The findings reveal that personality traits significantly influence internship attitudes, which in turn affect employability. These results provide novel theoretical insights into the psychological mechanisms underlying internship persistence and practical recommendations for optimizing vocational education and enhancing school-enterprise collaboration to better meet students' employability and career readiness needs.